Seasonal forecasting of Bactrocera dorsalis Hendel, 1912 (Diptera: Tephritidae) in bioclimatic zones of Sri Lanka using the SARIMA model - W. M. C. D. Wijekoon; G. A. S. M. Ganehiarachchi; H. C. E. Wegiriya; S. P. Vidanage (CABI Agriculture and Bioscience)
Abstract Bactrocera dorsalis Hendel is a severe fruit pest that causes significant economic losses globally. Despite B. dorsalis having been distributed mostly across Asia, studies on its current and future density variation in Sri Lanka are sparse to date. The present study was thus carried out to assess the contemporary density variation (2020–2022) and future density fluctuation (2023–2025) of B. dorsalis in bioclimatic zones of Sri Lanka. The density was assessed using the monthly-based fruit fly trap collection method from randomly selected 40 locations in all bioclimatic zones (wet, intermediate, dry, and arid). The SARIMA modelling technique was applied for delineating the best-fit model and for density forecasting in each bioclimatic zone. The density variations were depicted for the year and for the bioclimatic zone (2020–2025) by colour intensity maps using QGIS. According to the findings, B. dorsalis shows a seasonal component to its year-round density variation and an ascending trend in its density from 2020 to 2025. Density forecasting records a 20%, 30%, 26%, and 37% density increase in the wet, intermediate, dry, and arid zones, respectively, in 2025. In 2025, the highest predicted B. dorsalis density from the arid zone and the lowest predicted density from the wet zone were recorded. This study contains the first forecasting attempt for B. dorsalis density using the SARIMA approach as well as the application of colour-intensity depiction for its density variation in Sri Lanka, which leads decision makers and stakeholders in economic agriculture to plan the scientific management of B. dorsalis to avoid its current and potential future threat to the country’s fruit industry.